Clinical outcomes of liposomal irinotecan plus fluorouracil/leucovorin for metastatic pancreatic adenocarcinoma in patients previously treated with conventional irinotecan-containing chemotherapy. (March 2021) - Bang, Kyunghye; Cheon, Jaekyung; Jeong, Jae Ho; Im, Hyeon-Su; Kim, Kyu-pyo; Ryoo, Baek-Yeol; Yoo, Changhoon
Introduction: Liposomal irinotecan (nal-IRI) plus fluorouracil/leucovorin (5-FU/LV) has shown clinical benefit in patients with metastatic pancreatic adenocarcinoma (mPAC) who progressed on gemcitabine-based chemotherapy. However, its role in patients with mPAC previously treated with conventional irinotecan-containing chemotherapy has not been appropriately investigated. Methods: In this retrospective analysis, patients with mPAC who received nal-IRI plus 5-FU/LV after conventional irinotecan-containing regimen between January 2017 and March 2020, were identified from two referral cancer centers in South Korea. The ratio of time to progression (TTP) with nal-IRI plus 5-FU/LV to TTP with conventional irinotecan (TTPr) was analyzed with respect to the duration and cumulative dose of conventional irinotecan treatment. Results: In total, 35 patients treated with nal-IRI plus 5-FU/LV after the irinotecan-containing regimen were analyzed. The median age was 58 years and 16 (46%) patients were male. The median duration of conventional irinotecan therapy was 4.6 months at a median cumulative dose of 1230 mg. The objective response rate of nal-IRI plus 5-FU/LV was 2.9%, and stable disease was achieved in 11 (31.4%) patients. During the median follow-up of 9.2 [95% confidence interval (CI): 7.8–10.5] months, the median progression-free survival (PFS) and overall survival (OS) were 2.0 (95% CI: 1.4–2.6) months and 4.4 (95% CI: 3.6–5.7) months, respectively. The 6-month PFS and OS rates were 16.3% and 37.5%, respectively. The median TTPr was 0.41 (range, 0.07–2.07), showing a negative correlation with the cumulative dose of prior irinotecan therapy (R = −0.37, p  = 0.041). A tentative negative correlation between TTPr and duration of prior irinotecan therapy was observed ( R  = −0.35, p  = 0.062). The most common grade 3–4 toxicities were neutropenia (20%) and fatigue (8.6%). Conclusion: Nal-IRI plus 5-FU/LV showed modest effectiveness and manageable toxicities for patients with mPAC previously treated with conventional irinotecan-containing chemotherapy. The cumulative dose of prior conventional irinotecan therapy may be inversely correlated with the effectiveness of nal-IRI plus 5-FU/LV.